A retrospective evaluation of the aesthetics of the nasolabial complex after unilateral cleft lip repair using the Tennison-Randall technique: A study of 44 cases treated in a single cleft center - Iliopoulos, Christos; Mitsimponas, Konstantinos; Lazaridou, Dimitra; Neukam, Friedrich Wilhelm; Stelzle, Florian (Journal of Cranio-Maxillofacial Surgery, 2014)
Among numerous techniques that have been described for lip repair, the Tennison-Randall method has gained popularity over time and is preferred by many surgeons due to the predictability of the outcome. This study aims to evaluate the esthetic outcome reached in the nasolabial region following primary lip repair with the use of this method.Forty-four patients with unilateral cleft lip (with or without alveolar cleft) were assessed retrospectively through a photographic evaluation by two clinicians with regard to the aesthetics of the lip and nose separately as anatomical subunits as well as of the nasolabial region as an anatomical complex. The collected data were statistically analyzed with regard to the cleft subtype and the performance of corrective surgeries for the lip and/or the nose.The method was associated with good results, especially when it comes to the appearance of the nose as an anatomical subunit, as well as of the nasolabial region as a complex, regarding cleft lip patients without an alveolar cleft.The Tennison-Randall technique proved to be a very satisfying method in terms of the esthetic long-term outcome in our patient collective.
EVALuna2:24385

Investigation of the interplay between plasma lipids and macrophage polarization in small oral squamous cell carcinomas with different outcome: A pilot study of 17 cases - Iliopoulos, Christos; Weber, Manuel; Mitsimponas, Konstantinos; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Journal of Cranio-Maxillofacial Surgery, 2016)
Growing evidence suggests a correlation of alternative polarization of macrophages (M2) with a bad outcome of oral cancer. Macrophage polarization plays a significant role in the progression of hyperlipidemia and atherosclerosis, being influenced from plasma cholesterol. On the other hand plasma lipids have been studied epidemiologically as risk factors in carcinogenesis. Goal of our pilot study was the investigation of a possible association of plasma lipids with tumor outcome through their potential influence on macrophage polarization.17 patients with small pN0 OSCC with different clinical outcome, treated operatively without postoperative R(C)T constituted our patient collective. Plasma lipids (total cholesterol and triglycerides) were studied in relation to macrophage polarization (determined through the expression of CD68, CD11c, CD163 and MRC1 antibodies) and tumor outcome.Patients with pathological chronic course of either plasma cholesterol or triglycerides demonstrated an increased infiltration with alternatively polarized macrophages in their specimens. Patients with pathological chronic course of plasma cholesterol showed moreover a bad tumor outcome.A role of plasma lipids in the tumor outcome via alternative macrophage polarization could be assumed. A larger prospective study is needed to confirm our preliminary results.
EVALuna2:24403

Prognostic significance of macrophage polarization in early stage oral squamous cell carcinomas - Weber, Manuel; Iliopoulos, Christos; Moebius, Patrick; Buettner-Herold, Maike; Amann, Kerstin Ute; Ries, Jutta; Preidl, Raimund; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Oral Oncology, 2016)
Polarization of tumor infiltrating macrophages is associated with the prognosis of solid malignancies and correlates with the occurrence of lymph node metastases in oral squamous cell carcinomas (oscc). Early stage (T1/T2, N0) oscc are characterized by a good prognosis and can be cured by surgery. The postoperative regime usually contains no adjuvant radio-/chemotherapy. The current pilot study was conducted to elucidate whether macrophage polarization in tumor resection specimens and diagnostic biopsies of early stage oscc is associated with tumor outcome.Patients with T1/T2, N0, and R0>5mm oscc without adjuvant therapy and 3-year follow-up after tumor resection were retrospectively selected. Tissue microarrays (TMA) containing diagnostic biopsies (n=17) and tumor resection specimens (n=17) were processed for immunohistochemistry in this pilot study to detect CD68-, CD11c-, CD163- and MRC1-positive macrophages. Samples were digitized, and the expression of macrophage markers was quantitatively analyzed.High infiltration of M2 polarized macrophages correlated with poor tumor outcome in early stage (T1/T2, N0) oscc. This correlation was observed in tumor resection specimens, but was also observed in diagnostic biopsies. M2 macrophage polarization in biopsies - but not in tumor resection samples - correlated with high scores in tumor grading.Macrophage polarization in early stage oscc is a potential prognostic marker for tumor outcome. The correlation of M2 polarized macrophages with tumor outcome can already be detected in the initial biopsies. Furthermore, M2 polarization of macrophages in biopsies is associated with an increased dedifferentiation.
EVALuna2:24408

Search for a reliable model for bisphosphonate-related osteonecrosis of the jaw: establishment of a model in pigs and description of its histomorphometric characteristics - Mitsimponas, Konstantinos; Moest, T.; Iliopoulos, Christos; Rüger, Thomas; Müller, Christiane; Lutz, Rainer; Shakib, K.; Neukam, Friedrich Wilhelm; Schlegel, K. A. (British Journal of Oral and Maxillofacial Surgery, 2016)
The pathogenesis of bisphosphonate-related osteonecrosis of the jaw (BRONJ) remains unknown, and the development of a reliable experimental model would help to improve our understanding of it. We used 12 domestic pigs of which 6 made up the experimental group and were treated with zoledronate 4mg intravenously weekly for 5 weeks, while the control group (n=6) were given no drugs. On day 60 the right second maxillary and mandibular third molars were extracted. Thirty days later 3 animals in each group were killed; the rest were killed 90 days later. Histopathological specimens from the extraction sites were analysed for bone density, collagen architecture, density of osteons, and the amount of non-mineralised bone. Bone density, amount of non-mineralised bone, and density of osteons differed significantly between the 2 groups (p<0.001 in each case), but the chromatic pattern dictated by the collagen architecture did not. Our results correspond to the observations that have been made in patients with BRONJ, which means that the histomorphometric conditions seen in patients can be reproduced in this experimental setting.
EVALuna2:24425

The free scapular/parascapular flap as a reliable method of reconstruction in the head and neck region: a retrospective analysis of 130 reconstructions performed over a period of 5 years in a single department - Mitsimponas, Konstantinos; Iliopoulos, Christos; Stockmann, Philipp; Bumiller, Lars; Nkenke, Emeka; Neukam, Friedrich Wilhelm; Schlegel, Karl-Andreas (Journal of Cranio-Maxillofacial Surgery, 2014)
The scapular/parascapular free flap was described by Saijo in 1978 and has since then been widely used in reconstructive procedures.This is a retrospective study, describing our experience with the use of free scapula/parascapular flap in 130 reconstructions over a period of 5 years in the Department of Oral and Maxillofacial Surgery of the University Hospital of Erlangen. Demographical data, data regarding the underlying pathology, flap raising details, microvascular anastomoses, early and late postoperative complications will be presented.The flap was raised without problems and the donor site was primarily closed in all cases. Sixteen flaps required revision. Five transplants were lost (failure rate of 3.85%). Loss of part of the flap was observed in 3 cases (2.3%).The free scapula/parascapular flap is a versatile and reliable flap that can find many applications in the reconstruction of complex head and neck defects.
EVALuna2:24359